Ultraviolet detection characteristics of Pd/n-ZnO thin film Schottky photodiodes grown on n-Si substrates - Somvansh D.; Pandey A.; Jit S. (My University, 2025)
The paper reports the electrical and ultraviolet (UV) detection characteristics of Pd Schottky contacts on ZnO thin films synthesized by the simple thermal oxidation of vacuum deposited metallic Zn on n-Si (100) substrates without using any seed layer. The scanning electron microscopy (SEM) shows a homogenous surface morphology of the ZnO nanostructured thin films grown by the above method. Various electrical parameters such as the rectification ratio, reverse saturation current, barrier height and ideality factor of the Pd/ZnO thin film based Schottky diodes have been determined by using the thermionic emission model. The UV detection property of the Schottky diode under consideration has been investigated by using a UV lamp (Pin= 650 μW) with operating wavelength of 365 nm. An excellent value of responsivity (∼ 5.16 A/W) was observed in this study. © 2013 American Scientific Publishers.